Groundwater Pumping Is a Significant Unrecognized Contributor to Global Anthropogenic Element Cycles. Issue 3 (11th September 2018) - Stahl, Mason O.
Abstract: Quantifying anthropogenic contributions to elemental cycles provides useful information regarding the flow of elements important to industrial and agricultural development and is key to understanding the environmental impacts of human activity. In particular, when anthropogenic fluxes reach levels large enough to influence an element's overall cycle the risk of adverse environmental impacts rises. While intensive groundwater pumping has been observed to affect a wide‐range of environmental processes, the role of intensive groundwater extraction on global anthropogenic element cycles has not yet been characterized. Relying on comprehensive datasets of groundwater and produced water (groundwater pumped during oil/gas extraction) chemistry from the U.S. Geological Survey along with estimates of global groundwater usage, I estimate elemental fluxes from global pumping, consumptive use, and depletion of groundwater. I find that groundwater fluxes appreciably contribute to a number of elements overall cycles and thus these cycles were underestimated in prior studies, which did not recognize groundwater pumping's role. I also estimate elemental loadings to agricultural soils in the United States and find that in some regions, groundwater may provide a significant portion (more than 10%) of crop requirements of key nutrients (K, N). With nearly 40% of globally irrigated land under groundwater irrigation, characterizing nutrient and toxic element fluxes to these soils, which ultimately influence crop yields, is important to our understanding of agricultural production. Thus, this study improves our basic understanding of anthropogenic elemental cycles and demonstrates that quantification of groundwater pumping elemental fluxes provides valuable information about the potential for environmental impacts from groundwater pumping. Abstract : Article impact statement : Straightforward analysis reveals groundwater pumping is an important and previously unrecognized flux in global anthropogenic element cycles.